A preparation method of potassium-sulfur battery based on bifunctional carrier material

By using nitrogen-phosphorus co-doped porous carbon fibers with atomic dispersed tellurium as a carrier material in potassium-sulfur batteries, the problems of potassium dendrite growth, potassium polysulfide shuttle effect and low utilization rate of active sulfur are solved, and potassium- The high specific capacity of sulfur batteries and excellent cycle stability.

CN119170806BActive Publication Date: 2025-02-14CHINA JILIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411609991.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

In terms of electrochemical performance and safety, existing potassium-sulfur batteries have problems such as potassium dendrite growth, potassium polysulfide shuttle effect, and low utilization rate of positive electrode active sulfur, which affects their cycle stability and reaction rate.

Method used

Using nitrogen-phosphorus co-doped porous carbon fibers with atomic-grade dispersed tellurium as the carrier material for potassium-sulfur batteries, potassium is uniformly deposited by electrochemical deposition method, inhibit dendrites growth, and dispersed tellurium through micro, mesoporous structures and atomic-grade dispersed tellurium. Catalytic action accelerates the conversion of potassium polysulfide and improves the utilization rate of active sulfur.

Benefits of technology

The high specific capacity and excellent cycle stability of potassium-sulfur batteries are achieved, the growth of potassium dendrites and the shuttle effect of potassium polysulfide are avoided, and the reaction rate and rate performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170806B_ABST
    Figure CN119170806B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a potassium-sulfur battery based on a bifunctional carrier material, wherein nitrogen-phosphorus co-doped porous carbon fiber () with atomic-level dispersed tellurium is used as the carrier material for the positive and negative electrodes of the potassium-sulfur battery; on the one hand, potassium is uniformly deposited in the porous carbon fiber through an electrochemical deposition method to obtain a negative electrode, thereby effectively inhibiting the growth of potassium dendrites; on the other hand, small molecules are immobilized by the spatial confinement effect of the micro- and mesoporous structures to obtain a positive electrode, thereby improving the utilization rate of active sulfur in the positive electrode; through the synergistic effect of the positive and negative electrodes, the potassium-sulfur battery exhibits a higher specific capacity and excellent cycle stability, thereby providing a new idea for the development of alkali metal-sulfur battery systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy batteries, and more specifically to a method for preparing a potassium-sulfur battery based on a bifunctional carrier material. Background Art

[0002] With the rapid development of electric vehicles, portable electronic devices and large-scale energy storage systems, the market demand for energy storage technologies with high energy density and low cost has become more urgent. The development of environmentally friendly and excellent cycle performance battery technology has become a global research focus. The natural abundance of potassium is 2.1 , which is significantly cheaper than lithium. Potassium-sulfur batteries have abundant resources, low material costs, and a theoretical specific capacity of up to 1672 , which is much higher than traditional lithium batteries and can meet the energy storage needs of high energy density. The redox potential of potassium is -2.93 , close to lithium's -3.04 ,and Compared to and With weaker Acidic, solvated ion radius is smaller and the desolvation energy is lower, making the ions diffuse faster at the electrolyte / electrode interface. Therefore, potassium-sulfur batteries are expected to have excellent electrochemical performance and show significant application potential in grid regulation and large-scale energy storage systems.

[0003] Current potassium-sulfur batteries have some challenges in terms of electrochemical performance and safety. For example, the uneven deposition of potassium metal on the negative electrode easily generates dendrites, which may pierce the separator and cause a short circuit. At the same time, the volume change of potassium during the deposition / stripping process causes the solid electrolyte interface (SESI). ) destruction and reconstruction, thus affecting the cycle stability of potassium-sulfur batteries. When the positive electrode is discharged, once the sulfur is reduced to soluble potassium polysulfide (such as , , ), which diffuses to the negative electrode, exacerbating side reactions such as dendrite growth and electrolyte depletion, leading to irreversible loss of active materials, reducing efficiency and shortening battery cycle life. In addition, potassium polysulfide to the final product The slow conversion kinetics also affect the reaction rate and rate performance of potassium-sulfur batteries.

[0004] Aiming at the key scientific problems of the existing potassium-sulfur battery system, the present invention proposes to use nitrogen-phosphorus co-doped porous carbon fibers with atomically dispersed tellurium ( ) as the carrier material for the positive and negative electrodes of potassium-sulfur batteries. On the one hand, potassium is uniformly deposited on In, get The negative electrode can make the potassium ion flow evenly distributed and effectively inhibit the growth of potassium dendrites. Small molecules can be immobilized by spatial confinement of micro- and mesoporous structures ,get The positive electrode is accelerated by the anchoring effect of physical and chemical adsorption and atomic-level dispersed tellurium to The conversion of potassium polysulfide can alleviate the shuttle effect of potassium polysulfide and improve the utilization rate of active sulfur in the positive electrode. Through the synergistic effect of positive and negative electrodes, potassium-sulfur batteries show higher specific capacity and excellent cycle stability, providing new ideas for the development of alkali metal-sulfur battery systems. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a potassium-sulfur battery based on a bifunctional carrier material. The design and preparation of carrier materials solves the problems of potassium dendrite growth, potassium polysulfide shuttle effect, and low utilization rate of positive electrode active sulfur in existing potassium-sulfur batteries.

[0006] The present invention prepares atomically dispersed tellurium ( ) of nitrogen and phosphorus co-doped porous carbon nanofibers ( ) carrier material, when applied to the negative electrode, it is beneficial to the uniform distribution of potassium ion flow, improves the deposition and stripping behavior of potassium ions, and thus inhibits the formation of potassium dendrites. In addition, when applied to the positive electrode, by immobilizing small molecular sulfur on In addition, it reduces the production of potassium polysulfide intermediates and accelerates the conversion of potassium polysulfide to The synergistic effect of the two improves the cycle performance and capacity retention rate of potassium-sulfur batteries.

[0007] The present invention aims to develop a potassium-sulfur battery with simple process, low cost and excellent electrochemical performance, so as to meet the needs of large-scale energy storage systems.

[0008] The present invention provides a method for preparing a potassium-sulfur battery based on a bifunctional carrier material, which is characterized by being achieved by the following technical solutions:

[0009] S1: Preparation of composite materials: Porous carbon materials and commercial tellurium powder are placed at both ends of a corundum ark, respectively, with the tellurium powder placed upstream of the airflow. The corundum ark containing the sample is placed in a tube furnace, and heated to the target temperature at a set heating rate under an argon atmosphere. The temperature is kept constant for a period of time to complete the tellurium loading, and a precursor for making an electrode carrier material is obtained;

[0010] S2: Preparation of electrode carrier material: The composite material obtained in step S1 is placed in a tube furnace again, heated to a higher set temperature under an argon atmosphere, and kept warm for a period of time to remove tellurium atomic clusters, thereby obtaining a carrier material with atomically dispersed tellurium;

[0011] S3: Preparation of negative electrode: Cut the carrier material film obtained in step S2 into discs as working electrodes, match them with metal potassium sheets, add electrolyte and separator, assemble into a potassium metal battery, pre-cycle the battery under a set voltage range and current density to complete the activation of the carrier material, electrochemically deposit potassium after the pre-cycle, and control the deposition capacity of potassium, disassemble the battery after the deposition is completed, and recover the electrode as a self-supporting negative electrode of the potassium-sulfur battery;

[0012] S4: Preparation of positive electrode: The support material film obtained in step S2 is further used for small molecules Loading, first, placing the carrier material and the sulfur powder at the top and bottom of the polytetrafluoroethylene liner according to a set mass ratio, and sealing the reactor in a glove box to achieve argon filling, heating the reactor to a target temperature, and keeping it warm for a period of time to complete the sulfur loading, then placing the composite material in a tubular furnace, under an argon atmosphere, heating it from room temperature to a higher target temperature at a set heating rate, and keeping it warm for a period of time to remove the surface adsorbed sulfur, and finally obtaining a self-supporting positive electrode of a potassium-sulfur battery;

[0013] S5: Assembling of potassium-sulfur battery: The self-supporting positive electrode material of the potassium-sulfur battery prepared in step S4 is cut into discs, which are matched with the self-supporting negative electrode of the potassium-sulfur battery obtained in step S3. 3M potassium bis(fluorosulfonyl)imide / ethylene glycol diethyl ether ( ) electrolyte and glass fiber membrane diaphragm, and assembled into a potassium-sulfur battery using a 2032-type button cell case in an argon-filled glove box.

[0014] Furthermore, the carbon material includes porous carbon nanofibers, nitrogen and phosphorus co-doped porous carbon nanofibers, and commercial carbon cloth.

[0015] Furthermore, nitrogen-phosphorus co-doped porous carbon nanofibers and commercial tellurium powder were loaded into the two ends of the corundum ark at a mass ratio of 1:4, and then heated to 5 The heating rate is from 25 Heat to 480 , and keep warm for 17 hours to complete the tellurium loading.

[0016] Furthermore, after the carrier material obtained in step S1 is cooled to room temperature, it is again placed in a tube furnace and heated at 5 The heating rate is from 25 Heating to 650 , and keep warm for 2 hours to remove the tellurium atomic clusters and obtain a support material with atomically dispersed tellurium.

[0017] Furthermore, the holding time of step S1 and step S2 is determined according to the thermal stability of the carbon material.

[0018] Furthermore, in step S3, for the assembled potassium metal battery, at 0.01 to 3 Voltage range and 0.1 At a current density of 0.1, 5 pre-cycles were performed, and then Electrochemical potassium deposition was carried out at a current density of 4 .

[0019] Furthermore, The carrier material and commercial sulfur powder were placed on the top and bottom of the polytetrafluoroethylene liner at a mass ratio of 1:7, and the reactor was sealed in a glove box to achieve argon filling. The reactor was then transferred to a forced air drying oven and heated at 155 The sulfur loading was then completed by placing it in a tube furnace and heating it at 5 The heating rate is from 25 Heating to 250 , and keep warm for 2 hours to remove the sulfur adsorbed on the surface, and finally obtain Self-supporting positive electrode.

[0020] The advantages and positive effects of the present invention are:

[0021] The present invention applies a novel dual-functional carrier material to a potassium-sulfur battery, avoiding the use of a current collector, specifically:

[0022] In terms of the negative electrode, the carrier material has a unique hierarchical pore structure. The introduction of atomic-level dispersed tellurium further increases the interlayer spacing of the material, which provides sufficient space for the transmission of potassium ions and helps to evenly distribute the potassium ion flow. In addition, its three-dimensional network structure can effectively alleviate the volume change during the potassium deposition-stripping process, thereby ensuring the uniformity of potassium deposition and inhibiting dendrite growth.

[0023] In the positive electrode, the rich micro- and mesoporous structures on the support materials promote the small molecule The solid support and uniform distribution of tellurium can anchor the potassium polysulfide intermediates and reduce the influence of the shuttle effect. At the same time, the catalytic effect of atomically dispersed tellurium accelerates the potassium polysulfide to The conversion improves the utilization rate of active sulfur;

[0024] Potassium-sulfur batteries based on bifunctional support materials exhibit excellent electrochemical performance, including high reversible capacity and outstanding cycling stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The prepared in Example 1 Carrier material ( ) Transmission electron microscopy ( )、( ) Selected area electron diffraction ( )、( ) High-resolution transmission electron microscopy ( )and( ) Spherical aberration electron microscope ( )picture.

[0026] Figure 2 In Example 1 and Example 2 Battery, Battery, Battery at 1.5 Charge cut-off voltage, 0.5 Current density and 1.0 Coulombic efficiency change curve of potassium deposition-stripping under deposition area specific capacity.

[0027] Figure 3 The prepared in Example 1 negative electrode( ) and assembled into / / After 50 cycles of symmetrical battery ( ) of the scanning electron microscope ( )picture.

[0028] Figure 4 In Example 1 and Example 2 Symmetrical battery, Symmetrical battery, Symmetrical battery at 1.0 Current density and 1.0 Overpotential variation curve under area specific capacity.

[0029] Figure 5 The prepared in Example 1 Positive picture.

[0030] Figure 6 The prepared in Example 1 Positive electrode X-ray photoelectron spectroscopy ( ) characterization of S 2p spectrum.

[0031] Figure 7The four different potassium-sulfur battery systems in Example 1 and Example 2 (including Battery, Battery, Battery, Battery) in 0.3~3.0 Voltage range and 0.4 Cycling performance curves under different current densities. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the present invention. In addition, the forms of the various structures described in the following embodiments are only illustrative. The preparation method of a potassium-sulfur battery based on a bifunctional carrier material involved in the present invention is not limited to the various structures described in the following embodiments. All other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0033] Embodiment 1:

[0034] S1: Preparation Composite material, the specific process is as follows: 28.3 Nitrogen and phosphorus co-doped porous carbon nanofibers and high-purity bulk tellurium powder (99.999%) were placed at both ends of a corundum ark at a mass ratio of 1:4, with the tellurium powder located upstream of the gas flow. The corundum ark was placed in a tube furnace under an argon atmosphere at 5 The heating rate is from 25 Heat to 480 , and kept warm for 17 hours to complete the tellurium loading and obtain 42.38 .

[0035] S2: The obtained in step S1 After cooling to room temperature, it was put into the tube furnace again and heated from 25 Heating to 650 , and kept warm for 2 hours to remove the tellurium atomic clusters and obtain atom-dispersed tellurium Carrier material;

[0036] S3: After obtaining the above Based on the support material, potassium is electrochemically deposited to obtain a self-supporting , as the negative electrode of potassium-sulfur battery, the preparation process is as follows: The film is cut into 8 Electrode sheet, matched with metal potassium sheet, add 60 3 Electrolyte and glass fiber separator, use 2032 button battery case, assembled Battery. 0.01~3 Voltage range and 0.1 At a current density of 0.1, 5 pre-cycles were performed, and then Electrochemical potassium deposition was carried out at a current density of 4. After deposition is complete, the battery is disassembled and recycled. , as a self-supporting negative electrode for potassium-sulfur batteries;

[0037] S4: After obtaining the above Based on the carrier material, sulfur loading is carried out to prepare the small molecule carrier Self-supporting The specific preparation process of the positive electrode is as follows: 26.55 The film and commercial sulfur powder were placed on the top and bottom of the polytetrafluoroethylene liner at a mass ratio of 1:7, and the reactor was sealed in a glove box to achieve argon filling. The reactor was then transferred to a forced air drying oven and heated at 155 The sulfur loading was then completed by placing it in a tube furnace and heating it at 5 The heating rate is from 25 Heating to 250 , and kept warm for 2 hours to remove the sulfur adsorbed on the surface, and finally obtained 36.16 Contains small molecules Self-supporting positive electrode;

[0038] S5: Assembling the potassium-sulfur battery: Assemble the potassium-sulfur battery prepared in step S4. The material was cut into discs with a diameter of 8 mm and compared with the discs obtained in step S3. Negative electrode matching, select 3 Potassium bis(fluorosulfonyl)imide / ethylene glycol diethyl ether ( ) electrolyte and glass fiber membrane diaphragm, and assembled into a potassium-sulfur battery using a 2032-type button cell case in an argon-filled glove box.

[0039] Embodiment 2:

[0040] Nitrogen-phosphorus co-doped porous carbon nanofibers were prepared by electrospinning and high-temperature calcination. ) For the specific preparation process, please refer to patent: CN202210818642.7 as the carrier material, prepare the self-supporting type Negative electrode and Positive electrode: Except for the different carrier materials used, the other specific preparation processes are the same as Example 1.

[0041] Embodiment 3:

[0042] Porous carbon nanofibers were prepared by electrospinning and high-temperature calcination. The specific preparation process of porous carbon nanofibers (PCNFs) can be found in patent: CN202210818642.7. PCNFs were used as the carrier material, and high-purity bulk tellurium powder (99.999%) was used as the tellurium source. TePCNFs carrier material with atomically dispersed tellurium was prepared by two high-temperature calcination processes at different temperatures. On this basis, self-supporting Negative electrode and Positive electrode: Except for the different carrier materials used, the other specific preparation processes are the same as Example 1.

[0043] Embodiment 4:

[0044] Using commercial carbon cloth (CC) as a precursor and high-purity bulk tellurium powder (99.999%) as a tellurium source, a TeCC carrier material with atomically dispersed tellurium was prepared through two high-temperature calcination processes at different temperatures. On this basis, self-supporting K@TeCC negative electrodes and S@TeCC positive electrodes were prepared respectively; except for the different carrier materials used, the other specific preparation processes were the same as Example 1.

[0045] The batteries prepared in Example 1 and Example 2 were tested accordingly:

[0046] (1) Coulombic efficiency test of potassium deposition-stripping in potassium metal battery system:

[0047] Commercial copper sheets, and Cut into 8 in diameter The electrode is matched with potassium metal and 60 3 Electrolyte and glass fiber separator, use 2032 button battery case, assembled Battery, Batteries and Batteries. Battery, at 0.1 Constant current discharge at current density, controlling potassium deposition capacity to 4.0 ;for Batteries and Battery, 0.01~3 The voltage range is 0.1 The current density was used for 5 pre-cycles, and then potassium was electrochemically deposited at the same current density. The potassium deposition capacity was also controlled to be 4.0 Finally, the three battery systems were tested at 0.5 The current density and 1.0 Cyclic tests were performed at the deposition area specific capacity to evaluate the potassium , , Deposition-stripping efficiency on .

[0048] (2) Cyclic performance test of symmetrical battery system:

[0049] First, assemble Battery, Batteries and Battery, complete 4.0 After potassium deposition, the battery is disassembled and the self-supporting type containing potassium deposition is recovered. , , , use them as positive and negative electrodes at the same time, add 60 3 Electrolyte and glass fiber separator, use 2032 button battery shells were assembled in an argon-filled glove box. Symmetrical battery, Symmetrical battery and Symmetrical battery; finally, at 1.0 The current density and 1.0 Cyclic tests were performed at area-specific capacity to evaluate the overpotential changes of the symmetric battery system.

[0050] (3) Cyclic performance test of potassium-sulfur battery system:

[0051] First, assemble Battery, Batteries and Battery, complete 4.0 After potassium deposition, the battery is disassembled and the self-supporting type containing potassium deposition is recovered. , and The electrodes are used as the negative electrode of the potassium-sulfur battery, and the matching one is a self-supporting or As the positive electrode of potassium-sulfur battery, control the capacity ratio of negative electrode and positive electrode ( ratio) was 4:1; then, 60 3 Electrolyte and glass fiber separator, use 2032 button battery shells were assembled in an argon-filled glove box. Battery, Battery, Batteries and Battery, and in 0.3~3 Voltage range and 0.4 The cycling performance was evaluated at different current densities.

[0052] The samples prepared by the present invention are , , , To characterize its morphology, structure, and composition; use Battery tester at 25 The coulombic efficiency test of potassium deposition-stripping of potassium metal battery system, the cycle test of symmetric battery system and the constant current charge and discharge test of potassium-sulfur battery system were carried out under the conditions.

[0053] Figure 1 The prepared in Example 1 Carrier material , , and Fig. from ( Figure 1 A) You can see It has a fibrous structure and a porous structure with abundant pores on its surface. This structure not only helps to evenly distribute the potassium ion flow and inhibit the growth of potassium dendrites, but also facilitates the uniform loading of small molecular sulfur and enhances the adsorption of potassium polysulfide intermediates through the spatial confinement of micro- and mesopores, thereby improving the cycle stability of the potassium-sulfur battery. picture( Figure 1 B) A continuous diffuse ring can be observed, indicating that The material has an amorphous structure. picture( Figure 1 C) further confirmed its amorphous structure, which is beneficial to maintain the morphological stability of the electrode during the charge and discharge cycle; picture( Figure 1 The bright spots in D) represent atomic-level dispersion ,These Evenly distributed in superior.

[0054] Figure 2 In Example 1 and Example 2 Battery, Batteries and Battery at 1.5 Charge cut-off voltage, 0.5 Current density and 1.0 Coulombic efficiency change curve of potassium deposition-stripping under deposition area specific capacity. Figure 2 It can be seen that compared with Short cycle life and post-cycle period of batteries Fluctuation of battery coulombic efficiency, The battery can be stably cycled for 480 cycles with an average coulombic efficiency of nearly 99.1%; this proves The unique structural design can effectively alleviate the volume change of potassium during charging and discharging, thereby achieving highly reversible potassium deposition-stripping.

[0055] Figure 3 The prepared in Example 1 Before and after the cycle Fig. from Figure 3 A shows that when the potassium deposition capacity is 4 hour, The three-dimensional network structure of the carrier material is uniformly filled with potassium metal and has a uniform morphology, indicating that The support material supports uniform deposition of potassium. Figure 3 B knows that After 50 cycles, the symmetrical battery The electrode morphology did not change significantly, which was mainly due to the formation of a stable films and uniform potassium deposition / stripping behavior.

[0056] Figure 4 In Example 1 and Example 2 Symmetrical battery, Symmetrical battery and Symmetrical battery at 1.0 The current density and 1.0 Overpotential variation curve under area specific capacity. Figure 4 It can be seen that the order of overpotential at the beginning of the cycle is Symmetrical battery< Symmetrical battery< Symmetrical battery. As the cycle continues, The sudden drop in the overpotential of the symmetrical battery means that potassium dendrite growth has occurred, resulting in a micro-short circuit in the battery; The increase in the overpotential of the symmetric cell indicates an increase in the internal resistance of the cell, which may be caused by the large volume change during the potassium deposition-stripping process. The continuous destruction / reconstruction and electrolyte consumption; during the entire cycle, The overpotential of the symmetric cell remains relatively stable, which is mainly due to The introduction of atomic-level dispersed tellurium and the synergistic effect of the hierarchical porous carbon nanofiber structure provide excellent channels and guidance for the transport and deposition of potassium ions, while effectively alleviating the effects of volume expansion and interface stress on the electrode.

[0057] Figure 5 The prepared in Example 1 Positive Fig. Compared to Carrier materials (see Figure 1 shown), from Figure 5 It can be seen that after loading sulfur The morphology of the positive electrode did not change significantly, which is mainly due to the small molecules Occupied The micro- and mesopores of the carrier material help to anchor potassium polysulfide during the electrode reaction and alleviate the shuttle effect. The high conductivity of the support material improves the carrier transport inside the electrode, and the catalytic effect of atomically dispersed tellurium accelerates the transfer of potassium polysulfide to conversion, thereby improving Utilization of active sulfur in the positive electrode.

[0058] Figure 6 The prepared in Example 1 Positive electrode X-ray photoelectron spectroscopy ( ) characterization of S 2p spectrum. Figure 6 There are two obvious peaks, located at 164.1 and 165.3 , corresponding to The S 2p3 / 2 and S 2p1 / 2 peaks confirm that Covalent bonds and small molecules The existence of The porous structure and the introduction of atomically dispersed tellurium provide the sample with abundant active sites, thus achieving the effective loading of small molecule sulfur.

[0059] Figure 7 The four different potassium-sulfur battery systems in Example 1 and Example 2 (including Battery, Battery, Batteries and Battery) at 0.3~3 Voltage range and 0.4 Cyclic performance curve under current density. Figure 7 It can be seen that the order of cycle stability of the above potassium-sulfur battery system is Battery> Battery> Battery> After 120 cycles, the specific capacity is 1266.3 , 803.3 , 93.7 , 197.9 (Calculated based on the mass of sulfur in the positive electrode). Overall, The battery has the best cycle stability, with an initial specific capacity of 1584.1 , at 0.4 After 120 cycles at the same current density, the capacity retention rate is as high as 80%. In summary, this excellent electrochemical performance is mainly attributed to The dual functionality of the carrier material, in terms of the negative electrode, The three-dimensional hierarchical pore structure of the carrier material provides a good channel for potassium ion transmission, which can effectively alleviate the volume change during potassium deposition-stripping. The introduction of atomic-level dispersed tellurium not only expands the interlayer spacing of the material and improves the conductivity, but also promotes the uniform distribution of potassium ion flow, thereby effectively inhibiting Potassium dendrite growth at the negative electrode; for the positive electrode, The micro- and mesoporous structures on the carrier material have a confining effect, which promotes the On the other hand, it can anchor the potassium polysulfide intermediates produced during the electrode reaction, alleviating the shuttle effect. In addition, atomic-level dispersed tellurium also has a catalytic effect, promoting the conversion of potassium polysulfide to K2S and improving The utilization rate of active sulfur in the positive electrode. The synergistic effect of the two realizes the stable cycle of potassium-sulfur batteries during the cycle.

[0060] Finally: The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0061] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a potassium-sulfur battery based on a bifunctional carrier material, characterized in that: S1: Preparation of composite materials: Porous carbon materials and commercial tellurium powder are placed at both ends of a corundum ark, respectively, with the tellurium powder placed upstream of the airflow. The corundum ark containing the sample is placed in a tube furnace, and heated to the target temperature at a set heating rate under an argon atmosphere. The temperature is kept constant for a period of time to complete the tellurium loading, and a precursor for making an electrode carrier material is obtained; S2: Preparation of electrode carrier material: The composite material obtained in step S1 is placed in a tube furnace again, heated to a higher set temperature under an argon atmosphere, and kept warm for a period of time to remove tellurium atomic clusters, thereby obtaining a carrier material with atomically dispersed tellurium; S3: Preparation of negative electrode: Cut the carrier material film obtained in step S2 into discs as working electrodes, match them with metal potassium sheets, add electrolyte and separator, assemble into a potassium metal battery, pre-cycle the battery under a set voltage range and current density to complete the activation of the carrier material, electrochemically deposit potassium after the pre-cycle, and control the deposition capacity of potassium, disassemble the battery after the deposition is completed, and recover the electrode as a self-supporting negative electrode of the potassium-sulfur battery; S4: Preparation of positive electrode: The support material film obtained in step S2 is further used for small molecules Loading, first, the carrier material and the sulfur powder are placed on the top and bottom of the polytetrafluoroethylene liner according to a set mass ratio, and the reactor is sealed in a glove box to achieve argon filling, the reactor is heated to a target temperature, and kept warm for a period of time to complete the sulfur loading, then the composite material is placed in a tubular furnace, and in an argon atmosphere, the temperature is raised from room temperature to a higher target temperature at a set heating rate, and kept warm for a period of time to remove the surface adsorbed sulfur, and finally a self-supporting positive electrode of a potassium-sulfur battery is obtained; S5: Assembling of potassium-sulfur battery: The self-supporting positive electrode material of the potassium-sulfur battery prepared in step S4 is cut into discs, which are matched with the self-supporting negative electrode of the potassium-sulfur battery obtained in step S3. 3M potassium bis(fluorosulfonyl)imide / ethylene glycol diethyl ether ( ) electrolyte and glass fiber membrane diaphragm, and assembled into a potassium-sulfur battery using a 2032-type button cell case in an argon-filled glove box.

2. The method for preparing a potassium-sulfur battery based on a bifunctional carrier material according to claim 1, characterized in that: The carbon material includes porous carbon nanofibers, nitrogen and phosphorus co-doped porous carbon nanofibers, and commercial carbon cloth.

3. The method for preparing a potassium-sulfur battery based on a bifunctional carrier material according to claim 2, characterized in that: Nitrogen and phosphorus co-doped porous carbon nanofibers and commercial tellurium powder were loaded into the two ends of the corundum ark at a mass ratio of 1:

4. The heating rate is from 25 Heat to 480 , and keep warm for 17 hours to complete the tellurium loading.

4. The method for preparing a potassium-sulfur battery based on a bifunctional carrier material according to claim 3, characterized in that: After the carrier material obtained in step S1 was cooled to room temperature, it was put into the tube furnace again and heated at 5 The heating rate is from 25 Heating to 650 , and kept warm for 2 hours to remove the tellurium atomic clusters and obtain a support material with atomically dispersed tellurium.

5. The method for preparing a potassium-sulfur battery based on a bifunctional carrier material according to claim 2, characterized in that: The holding time of step S1 and step S2 is determined according to the thermal stability of the carbon material used.

6. The method for preparing a potassium-sulfur battery based on a bifunctional carrier material according to claim 1, characterized in that: In step S3, for the assembled potassium metal battery, to 3 Voltage range and 0.1 At a current density of 0.1, 5 pre-cycles were performed, and then Electrochemical potassium deposition was carried out at a current density of 4 .

7. The method for preparing a potassium-sulfur battery based on a bifunctional carrier material according to claim 6, characterized in that: The carrier material and commercial sulfur powder were placed on the top and bottom of the polytetrafluoroethylene liner at a mass ratio of 1:7, and the reactor was sealed in a glove box to achieve argon filling. The reactor was then transferred to a forced air drying oven and heated at 155 The mixture was placed in a tube furnace and heated at 5 °C for 12 h under an argon atmosphere. The heating rate is from 25 Heating to 250 , and keep warm for 2 hours to remove the sulfur adsorbed on the surface, and finally obtain Self-supporting positive electrode.

Citation Information

Patent Citations

  • Electrode based on sub-nano tellurium and graded pore carbon fiber and preparation method thereof

    CN115148956A

  • Sulfur-carbon composite cathodes in carbonate electrolyte for lithium-sulfur batteries

    US20240372149A1